EXAMINATION OF SOME HAEMATOLOGIC AND CHEMICAL INDICES IN WOMEN TAKING HORMONAL CONTRACEPTIVE OR USING AN INTRA-UTERINE DEVICES - A.Majd; Gh. Jalali; K.Montazami (Tehran University of Medical Sciences, 1973)
A total number of 124 women of childbearing age attending a family planning clinic in Teheran were investigated for the effects of contraceptive steroids and the intra-terine device on their Hemoglobin concentration, packed cell volume, Serum Iron and serum TIBC. A total of 42 women were used as control group of 42 women who were fitted with an intra-uterine device, 17 were studied for changes in their blood picture or the first 6 months -2 years of use. There was a drop in their mean Hb oncenuration from 14.2 gm to 12.6 gm (the difference is statistically significant), with changes in CV. Serum Iron and TIBC suggesting some degree of Iron deficiency anemia. In mmunities where levels of Hb tend to be lower than those of the present study, use of unsuitable IUD may precipitate severe degrees of Iron deficiency anemia. Forty-one omen were studied for effects of hormonal contraceptives on their blood picture for the first 6 months and for 6 months -2 years of use- There was a slight rise of the mean Hb from 14.1 to 14.3, although elevation of the mean PCV was more marked from 35.2 to 37.5 There was a marked elevation of Serum TIBC reaching levels higher than the normal 506.6 after 6 months of use (the difference is statistically significant), with one elevation in Serum Iron. These changes may be due to the combined effects of estrogens and progesterone in increasing the red cell volume and the balance of Iron between extra cellular fluid and Iron stores - Therefore, contraceptive pill should not be recommended for the sole reason of improving the hemoglobin levels of a community.